Implementasi Aplikasi Ngajikuy Dalam Pembelajaran Pendidikan Agama Islam Dan Dampaknya Terhadap Motivasi Belajar Siswa Di Kb TK Al Hanif - Rasyid Nata Mulyana; Djogi Banyu Adem (Maslahah: Jurnal Pengabdian Masyarakat, 2023)
The purpose of the Community Partnership Program (PKM) implementation is to test the Ngajikuy application on students at KB TK Al Hanif and measure its impact on their learning motivation. The method used in this activity is the experimental method, which is demonstrated by showing how to learn to read using the Ngajikuy application on students and teachers. The results of this activity can be concluded that the use of the Ngajikuy application in learning can improve the quality of learning and increase the learning motivation of students at KB TK Al Hanif compared to conventional media.